Remedying the Hummingbird Cryptographic Algorithm - B.Vishwa Teja, R.G.Kalyan Sreenivas, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the present current life, there is evermore care is expected to ensure data. Therefore, it is important to consider the cryptographic algorithms. The different cryptographic algorithms like AES, DES have been neglected to meet the necessities of low-level devices particularly in the control systems, and this prompts the advancement of super lightweight cryptography. Lightweight cryptography is the new region in the field of cryptography. These lightweight cryptographic algorithms attempt to decrease area and power requirements, with less an ideal opportunity for handling. This prompts minimal expense execution. Hummingbird cryptography is one such strategy.Different lightweight cryptographic algorithms are examined momentarily, these algorithms utilize either block cipher or stream cipher yet the hummingbird is the uncommon lightweight cryptography since it utilizes the highlights of both block and stream cipher. Accordingly, it gives better security to less-resourced devices in examination with the other lightweight algorithms. The hummingbird algorithm is now planned and created on various stages like microcontroller, ASIC execution, and so forth, and it is examined momentarily.